2000
DOI: 10.2136/sssaj2000.6441330x
|View full text |Cite
|
Sign up to set email alerts
|

Artifacts Caused by Collection of Soil Solution with Passive Capillary Samplers

Abstract: Soil solution was collected with passive capillary samplers of sampling is unknown and may change with varying (PCAPS) and zero-tension samplers (ZTS) from A horizons of forested soils. The volume and chemistry of collected solutions were moisture conditions or suction applied. In addition, sucmeasured weekly during discrete seasonal collection periods. Acidtion must be applied manually to the sampler several washed PCAPS increased alkalinity (3-fold), pH (1-3 units), and hours or days prior to solution collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 23 publications
4
48
0
Order By: Relevance
“…2). This corroborates the findings of Goyne et al (2000) and Brahy and Delvaux (2001) of cations sorbed to the wick surface. The measured and modeled water retention characteristics of the fiberglass wick are shown in Fig.…”
Section: Wick Characterizationsupporting
confidence: 91%
See 2 more Smart Citations
“…2). This corroborates the findings of Goyne et al (2000) and Brahy and Delvaux (2001) of cations sorbed to the wick surface. The measured and modeled water retention characteristics of the fiberglass wick are shown in Fig.…”
Section: Wick Characterizationsupporting
confidence: 91%
“…We L Ϫ1 colloid suspension for two to four pore volumes. Effluent pH was determined with a pH meter, and colloid concentratreated the wick with a procedure described by Goyne et al (2000). The wicks were first cut into 77-cm-long pieces, weighed, tions were determined spectrophotometrically at 300-nm wavelength, except the ferrihydrite, which was measured at and rinsed extensively with deionized water and combusted in a kiln at 400ЊC for 4 h. The wicks were weighed after combustion 214 nm.…”
Section: Wick Treatment and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the cup material (materials used include aluminium oxide, glass sinter, ceramic, teflon, acrylic copolymer with internal nylon support, stainless steel, plastic 'organic' polymers -PVC, PP, PVDF) additional reactions may take place leading to absorption, precipitation or even release of chemical substances, resulting in pronounced effects on the final composition of the water sampled (Litaor, 1988). Several studies have investigated these effects and questioned the validity of results given by these kinds of samplers (e.g., Hansen and Harris, 1975;Levin and Jackson, 1977;Nagpal, 1982;Guggenberg and Zech, 1992;Goyne et al, 2000). Siemens and Kaupenjohann (2003) found that between 0.8 and 63 mg L -1 of dissolved organic carbon (DOC) was released from sealing and glues of pore water samplers.…”
Section: Tension Samplersmentioning
confidence: 99%
“…To further remove carbonates and combustion residue, the fiberglass wicks were soaked in a 10 mM HNO 3 solution bath, as described by Goyne et al (2000). Once the pH stabilized at the initial concentration of nitric acid (typically pH of approximately 2), double-deionized water was substituted for the nitric acid bath solution.…”
mentioning
confidence: 99%